FPL - The football league that time forgot - Kamal, Rajiv (University of the Witwatersrand, Johannesburg, 2024)
I chose to do my Master’s long-form essay on the Federation Professional League (FPL). I have charted the legacy the league has left behind in terms of its history, players and impact. The FPL used sport as a tool to promote non-racialism and bring different racial groupings together. Despite there being not much recorded history about the league, the popularity and memories of it among some communities endures. While weaving in some aspects of history, which is essential to contextualise the overall story, I focused heavily on the players themselves and their experiences. Their motivations for playing in the FPL, their triumphs and defeats, the adversity they faced and what playing football in that particular league meant to them. It resulted in some incredibly varied and interesting stories – many of the former players and administrators have sharp memories and recall much of their experiences. I’ve also obtained a ‘third-eye’ perspective on the FPL, from former Post Newspaper Editor Brijlall Ramguthee who covered the league and knew many players and administrators. It was important for me to record the accounts of those still available before that history is lost forever. From a research perspective I focused on the popularity of soccer/football, nostalgia around the beautiful game, how psychology plays a role in how someone chooses to support a sports team or league, the significance of the World Cup in 2010 and the mythology behind sport – why do we remember players and sport events in a certain way and if that memory may not be perfectly accurate, does it diminish the story any less?
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Football; soccer; apartheid; sport; non-racial; FIFA; World Cup; South Africa Federation Professional League; SDG-4: Quality education